IFPA Senior Award Lecture: making sense of pre-eclampsia - two placental causes of preeclampsia? - Redman, C; Sargent, I; Staff, A (2014)
Incomplete spiral artery remodelling is the first of two stages of pre-eclampsia, typically of early onset. The second stage comprises dysregulated uteroplacental perfusion and placental oxidative stress. Oxidatively stressed syncytiotrophoblast (STB) over-secretes proteins that perturb maternal angiogenic balance and are considered to be pre-eclampsia biomarkers. We propose that, in addition and more fundamentally, these STB-derived proteins are biomarkers of a cellular (STB) stress response, which typically involves up-regulation of some proteins and down-regulation of others (positive and negative stress proteins respectively). Soluble vascular growth factor receptor-1 (sVEGFR-1) and reduced growth factor (PlGF) then exemplify positive and negative STB stress response proteins in the maternal circulation. Uncomplicated term pregnancy is associated with increasing sVEGFR-1 and decreasing PlGF, which can be interpreted as evidence of increasing STB stress. STB pathology, at or after term (for example focal STB necrosis) demonstrates this stress, with or without pre-eclampsia. We review the evidence that when placental growth reaches its limits at term, terminal villi become over-crowded with diminished intervillous pore size impeding intervillous perfusion with increasing intervillous hypoxia and STB stress. This type of STB stress has no antecedent pathology, so the fetuses are well-grown, as typifies late onset pre-eclampsia, and prediction is less effective than for the early onset syndrome because STB stress is a late event. In summary, abnormal placental perfusion and STB stress contribute to the pathogenesis of early and late onset pre-eclampsia. But the former has an extrinsic cause - poor placentation, whereas the latter has an intrinsic cause, 'microvillous overcrowding', as placental growth reaches its functional limits. This model explains important features of late pre-eclampsia and raises questions of how antecedent medical risk factors such as chronic hypertension affect early and late sub-types of the syndrome. It also implies that all pregnant women may be destined to get pre-eclampsia but spontaneous or induced delivery averts this outcome in most instances.